Evaluation of viability, metabolic activity and spore quantity in clostridial cultures during ABE fermentation - Kolek, Jan; Branska, Barbora; Drahokoupil, Marek; Patakova, Petra; Melzoch, Karel (FEMS microbiology letters, 2016)
Flow cytometry, in combination with fluorescent staining, was used to evaluate population heterogeneity in acetone-butanol-ethanol fermentation that was carried out with type strain Clostridium beijerinckii NCIMB 8052 and non-type C. pasteurianum NRRL B-598. A combination of propidium iodide (PI) and carboxyfluorescein diacetate (CFDA), PI plus Syto-9 and bis-oxonol (BOX) alone were employed to distinguish between active and damaged cells together with simultaneous detection of spores. These strategies provided valuable information on the physiological state of clostridia. CFDA and PI staining gave the best separation of four distinct subpopulations of enzymatically active cells, doubly stained cells, damaged cells and spores. Proportional representation of cells in particular sub-regions correlated with growth characteristics, fermentation parameters such as substrate consumption and product formation in both species under different cultivation conditions.
Keywords: spory bakteriální; Butanols; fermentace; mikrobiální viabilita; butanol; ABE; aceton; ethanol; Clostridium; glukosa; Microbial Viability; biomasa; clostridium; Acetone; butanoly; Energy Metabolism; Fermentation; energetický metabolismus; Spores, Bacterial; Flow Cytometry; flow cytometry; Glucose; Bioreactors; průtoková cytometrie; Ethanol; Biomass; viability; bioreaktory